Analyzing Exception Flows of Aspect-Oriented Programs - Coelho, Roberta; Staa, Arndt von; Rashid, Awais (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2009: Anais do XXII Concurso de Teses e Dissertações, 2009)
The goal of exception handling mechanisms is to make programs more reliable and robust. However, the integration of exception handling mechanisms with aspect-oriented languages raises unique issues. This paper presents a PhD work whose goal was to investigate such issues. The main contributions of this work were the following: (i) to perform the first exploratory study aiming at assessing the error proneness of AOP mechanisms on exception flows of programs; (ii) the development of SAFE (Static Analysis for the Flow of Exceptions), an exception-flow analysis tool for AspectJ programs; (iii) the identification of a set of bug patterns on the exception handling code of AO systems; and (iii) the definition of an approach that enables the developer to find faults on the exception handling code statically.